Delinquency, unstructured socializing, and social change: the rise and fall of a teen culture of independence - Osgood, D. Wayne (Criminology, 2023)
This article delves into the connections between time trends in unstructured socializing and other dramatic changes in adolescence since the 1950s. Osgood et al.’s (1996) individual-level application of routine activity theory proposed that unstructured socializing contributes to crime by exposing people to situations conducive to deviance, and a large body of research supports this idea. Unstructured socializing has proven useful as an explanatory bridge that links crime and deviance to key social factors like age, class, and gender. The present article expands on two recent studies (Baumer et al., 2021; Svensson & Oberwittler, 2021), which showed that changing rates of unstructured socializing help explain time trends in delinquency as well. Based on time trends across many domains of adolescent life, I argue that changes in unstructured socializing were a manifestation of the rise and fall of a teen culture of independence from the 1950s to the 2020s. The effectiveness of unstructured socializing as an explanatory bridge demonstrates the value of focusing on ordinary, everyday activities for tapping into features of life that are consequential and that vary across social conditions.